Management of Cross-cultural Communication Barriers for Indonesian Migrant Workers in South Korea - Nabilla Anasty Fahzaria; Sri Suwarsi; Sarah Annisa Fadhila; Wahyu Pebriyanto (Komunikator, 2024)
Indonesia, as a developing country, continues to grapple with a variety of labor challenges, including high unemployment rates and job scarcity. South Korea stands out as one of the destinations with a substantial presence of foreign migrant workers, including those from Indonesia. According to the Embassy of the Republic of Indonesia, the number of legal Indonesian citizens in South Korea has reached 37,000. Undoubtedly, Indonesian migrant workers encounter cross-cultural communication barriers in South Korea. This research aims to explore the cross-cultural communication challenges faced by Indonesian Migrant Workers (IMWs) in South Korea and examine the strategies they employ to manage these barriers effectively. Adopting a qualitative approach with a phenomenological method, data is gathered through interviews with Indonesian migrant workers from the fisheries, manufacturing, and tourism sectors in South Korea. The findings reveal that cultural disparities pose the primary challenge for IMWs in South Korea, affecting communication and causing discomfort. IMWs employ various strategies to address these communication barriers, focusing on managing language differences, adapting to work cultures, and fostering social networks to alleviate uncertainty and anxiety.